Barong Sebagai Simbol Pemersatu dan Kerukunan Umat Hindu Di Bali : Studi pada Ritual Paruman Barong di Pura Luhur Natar Sari, Desa Apuan, Kabupaten Tabanan - Bontot, I Nyoman (Institut Hindu Dharma Denpasar, 2020)
Conflict does not only occur in heterogeneous communities such as Indonesia, but also in homogeneus communities, including conflicts between villages and crowded places such as during the barong meeting ritual at Pura Luhur Natar Sari, Apuan Village, Baturiti District, Tabanan Regency. A ritual attended by 55 – 67 barongs with the capavity of the surrounding temples 50 barongs, thousands of barong accompanists and visitor (ppemedek), and the work (karya) committee. However, so far there has been almost no conflict. The absence of conflict in these rituals requires in depth research and study. This research presents the concepts of barong, barong meeting, symbols, unity, and harmony. The problem is studied using an eclectic theory, namely Structuration Theory and Deconstruction Theory. This research is classified as qualitative research and supported by qualitative data, collected through participatory observation techniques, in-depth interviews, and documentation studies. Unity and harmony between barong followers, visitors, dan work (karya) committee members can be realized, because of the belief that Ida Bhatara (manifestation of God) symbolized in the form of barong is one (God is only One), so they are all brothers and sisters. The presence of barong and rangda from 5 districts in Bali at the time of piodalan ageng (big festival), because each of these barongs begged for the regent at the Luhur Natar Sari Temple, and meant reuniting the manifestation of Ida Bhatara (Durga Dewi) in the Luhur Natar Sari Temple, which is worshiped in various forms (rangda, barong ket, barong macan, barong naga, barong landing) in various villages in five districts in Bali.